Estrogen and genistein modulation of bone homeostasis in the teleost, sea bass Dicentrarchus labrax: a proteomic approach - Santos, Rui Miguel Rodrigues dos (2015)
The skeleton in vertebrates is in constant turnover and functions as a reservoir of minerals. The regulation of bone turnover in vertebrates is a complex process and diet and hormones have a central role. Estrogen, a steroid, which signals via multiple nuclear and membrane receptors, is important in the turnover of bone in vertebrates. In humans lack of estrogen causes osteoporosis (bone thinning). The way in which estrogen regulates bone turnover is still relatively poorly described. The present thesis reports an experiment performed to assess how estrogen and the phytoestrogen, genistein, affect the bone proteome of a teleost, the sea bass, Dicentrarchus labrax. For the experiment an intraperitoneal injection of 17-β-estradiol (E2) (5mg/Kg body mass), Genistein (5mg/Kg body mass) and coconut oil (the vehicle) was administered to 30 immature sea bass (10 for each treatment) for 5 days and samples of blood and bone were collected. Plasma parameters like calcium, estrogen and vitellogenin were significantly (p<0.05) increased by E2. Genistein only increased vitellogenin. The two treatment did not modify bone metabolism and tartrate-resistant acid phosphatase (TRAP) and alkaline phosphatase (ALP) did not change significantly between treatment groups. Vertebral bone proteome was established and a total of 285 protein spots were detected and used for comparison between experimental groups. Analysis of the gels showed that 8 and 22 protein spots were differentially expressed (p<0.05) in vertebra from E2 and genistein treatment respectively. Of the 8 protein modified by E2, only 4 were identified. In the genistein treatment, of the 22 proteins differentially expressed only 10 were identified and 2 were the same as found in the E2 group Tropomyosin alpha-4 chain (TPM4) and Myosing binding protein C cardiac type like (MYPCL3). Identification and biological process were described using Uniprot, NCBI and gene ontology. Proteins differentially expressed in both treatments that were down-regulated were related to calcium ion binding, muscle contraction, cell adhesion, transport, protein targeting and homeostasis. In conclusion E2 and genistein did not modify indicators of bone turnover but modifications in the bone proteome occurred. A final step still required is the validation of the proteome results by Western blotting of selected proteins.